Video Head Impulse Test (vHIT) and Vestibular Evoked Myogenic Potential (VEMP) Test for Assessment of Vertigo: Our Initial Experience - Raquib, Ahmed; Harun, Md Abdullah Al; Matin, MA; Pramanik, Dhiman; Hafiz, M Muinul (Bangladesh Journal of Otorhinolaryngology, 2020)
Introduction: Loss of balance causes the sensation of vertigo. Balance is maintained by vestibular afferent from labyrinth, eyes and proprioceptors and their central integration. For diagnosis of vertigo, along with history different vestibulometric tests can be done to identify the specific anatomical part that is involved. Material and methods: A cross sectional study was done among 82 patients who did video Head Impulse Test (vHIT) and among 75 patients who did Vestibular Evoked Myogenic Potential (VEMP) test at AudiovestibularCentre(AVC) at Bangladesh ENT Hospital Ltd. during the period from April 2018 to September 2019. Results: Age range of the sample was 16 to 80 years. Among the 82 patients who did vHIT 62(75.6%) had abnormality in either Semi Circular Canal. Among 75 patients who did VEMP 27(36%) were detected to have abnormality in either in saccule or utricle. Conclusion: For diagnosis of cause of vertigo the appropriate test for individual part of vestibule is essential. vHIT and VEMP are two tests which are complementary to each other in explaining common peripheral causes of vertigo. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 5-9